Peranan Komunikasi Organisasi dalam Peningkatan Kualitas Pelayanan di Kecamatan Bolaang Itang Barat Kabupaten Bolaang Mongondow Utara - Diana, Amna; Lumolos, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The aims of this study are to know the role of organizational communication in the improvement of service quality in the West Bolang Itang District, the impact of organizational communication satisfaction, and the factors supporting the communication services organization in the process. The method used in this study put more emphasis on qualitative research methods. The instruments used in this study were a list of questions with emphasis on the various lists of questions that have been circulated to the informant in a structured or unstructured. The data collection techniques were observation and interviews. The observation was conducted in a participatory manner, in which researchers directed the targeted research communities. The analytical techniques used in this study were more emphasis on qualitative analysis. Â From this study it can be concluded that a) the role of organizational communication in the organization's service process can be applied through the relationship between superiors and subordinates, to maximize the timeliness of the work, affecting the attitude of openness subordinates in performing duties, affecting the administrative service, increasing the level of professionalism through education, and maximize the implementation of the discipline, b) good organizational communication satisfaction can affect the quality of service that can be seen from the procedure of service satisfaction, satisfaction in meeting the requirements of the various forms of service, satisfaction in the provision of cost of service, and satisfaction with services completion time, c) factors that supports communication between other organizations through service accountability, transparency of service, knowledge and skill factors and factors of discipline in conducting the service. It can be suggested that it is necessary to create Â a good working relationship between superior and subordinate, between subordinates with subordinates as well as between the parties nor the providers of service recipients, as well as a need for improvement in facilities and infrastructure to support the intensity of service activity. Keywords: role of organizational communication, service quality